2015
DOI: 10.1371/journal.pbio.1002076
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Alliance of Regulatory Pathways in C. albicans during Mammalian Infection

Abstract: Gene expression dynamics have provided foundational insight into almost all biological processes. Here, we analyze expression of environmentally responsive genes and transcription factor genes to infer signals and pathways that drive pathogen gene regulation during invasive Candida albicans infection of a mammalian host. Environmentally responsive gene expression shows that there are early and late phases of infection. The early phase includes induction of zinc and iron limitation genes, genes that respond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(135 citation statements)
references
References 47 publications
10
125
0
Order By: Relevance
“…Our studies reveal two faces of host Cu during infection with C. albicans: while serum Cu elevates, Cu can become limiting at the major site of infection in the kidney. As one possibility, the host may intentionally restrict Cu as part of an innate nutritional immunity response, similar to host withholding of Fe, Mn, and Zn for invading microbes (3)(4)(5)(6)(7)(8)(9)(10). Recent studies by Brown and colleagues have shown that during C. albicans infection of the kidney, Fe moves away from sites of fungal lesions in the cortex to the medulla as an apparent mechanism for Fe withholding (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies reveal two faces of host Cu during infection with C. albicans: while serum Cu elevates, Cu can become limiting at the major site of infection in the kidney. As one possibility, the host may intentionally restrict Cu as part of an innate nutritional immunity response, similar to host withholding of Fe, Mn, and Zn for invading microbes (3)(4)(5)(6)(7)(8)(9)(10). Recent studies by Brown and colleagues have shown that during C. albicans infection of the kidney, Fe moves away from sites of fungal lesions in the cortex to the medulla as an apparent mechanism for Fe withholding (9).…”
Section: Resultsmentioning
confidence: 99%
“…As part of the innate immune response, the host deliberately withholds metals, such as Fe, Zn, and Mn, from invading microbes in a process known as "nutritional immunity" (3)(4)(5). Like other infectious agents, C. albicans is equipped to handle restrictions placed on these micronutrients and can activate diverse pathways for scavenging host sources of Fe and Zn (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Profiling can be performed by assessing genome-wide transcription by using microarrays (195,200,(244)(245)(246)(247)(248), NanoString nCounter technology (249,250), and RNA sequencing (RNA-Seq) (197,200) or by using quantitative reverse transcription-PCR (RT-PCR) or Northern blot analysis of a smaller, select group of genes (251). Such comparisons are often made between biofilm preparations and planktonic cultures.…”
Section: Methods For Measuring Biofilms May Be a Source Of Variabilitymentioning
confidence: 99%
“…Distinct features of the infection environment have been revealed by diverse approaches that include histological analysis [23,24], imaging mass spectrometry [25], and transcriptional profiling [26]. We have previously used transcriptional profiling to understand the genetic control of pathogenicity in infected tissue [8,27,28]. We have found that many mutants that are defective in proliferation during infection present alterations of gene expression that can reveal the role of the mutated gene in pathogenicity.…”
Section: Introductionmentioning
confidence: 99%